Autoimmune and Paraneoplastic Myelopathies - Zalewski, Nicholas L.; Flanagan, Eoin P. (Seminars in Neurology, 2018)
Prompt recognition of an inflammatory myelopathy is critical, as a specific diagnosis and management plan allows for optimal patient outcomes. Many treatment options are now available for autoimmune and paraneoplastic myelopathies, but specific management strategies and expected prognosis vary widely depending on the underlying etiology. An understanding of the relevant clinical details, imaging findings, and other diagnostic information that can help achieve a specific myelopathy diagnosis and treatment plan is essential for all neurologists, given the variety of contexts in which myelopathies are encountered. We provide an outline of the diagnostic evaluation and treatment of various inflammatory myelopathies seen in autoimmune and paraneoplastic diseases, including multiple sclerosis, aquaporin-4 immunoglobulin G (IgG) seropositive neuromyelitis optica spectrum disorder, sarcoidosis, myelin oligodendrocyte glycoprotein IgG associated disease, and other rare inflammatory myelopathies; we also highlight common mimickers of inflammatory myelopathies.
Keywords: transverse myelitis; spinal cord; neuromyelitis optica